Nilai-Nilai Etika dalam Film Bajrangi Bhaijaan Perspektif Aristoteles dan Relevansinya terhadap Agama Islam - Azhari, Wulan; Kanus, Oktari (TSAQOFAH, 2025)
This study aims to analyze Aristotle's Virtue Ethics theory as portrayed in the film Bhajrangi Bhaijaan and to examine its relevance to Islamic Religious Education. The research is grounded in the importance of instilling universal moral values in education and explores how popular media such as film can represent ethical principles that align with Islamic teachings. A qualitative method with a content analysis approach was employed. The primary data source is the film Bhajrangi Bhaijaan directed by Kabir Khan, supported by secondary data from relevant literature, including journals, books, articles, and previous studies. Data collection was conducted through observation and documentation, encompassing preparation, implementation, and completion phases. The findings reveal that five core aspects of Aristotle’s Virtue Ethics, courage, generosity, justice, modesty, and benevolence are explicitly depicted in various scenes throughout the film. The film not only illustrates noble behavior consistent with Aristotle’s virtues but also conveys universal messages of humanity, compassion, and mutual assistance. In the context of Islamic Religious Education, these values hold strong relevance, as all of the aforementioned virtues are emphasized in the Qur’an and Hadith. Thus, the film can serve as a contextual learning medium to strengthen Islamic character formation and broaden students' understanding of ethical values across cultures.